PENGHAYATAN JANJI PERKAWINAN PASANGAN SUAMI ISTRI PEDESAAN DI TENGAH PERKEMBANGAN MEDIA KOMUNIKASI SOSIAL - Artzie, Scolastika Laras Ayu; Wijaya, Albert I Ketut Deni (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2021)
The aim of this research is mainly to know on how the Catholic Couples who live in rural areas in internalizing the marriage vows in the middle of applies the Qualitative method with purposive sampling couples at Saint Hilarius Parish - Klepu, age for marriage ranges from 5-15 years. The results of this research have shown that marriage vows being internalized as a holy bond, as moral and spiritual responsibility, as well as commitment and a lifelong faithfulness. Sosial media is used widely as a communication tool, mainly to keep bond when being far from each other and strengthening the relationship. However, social media also can give negative impact, such as to reduce quality direct interactions and as an opening potential to the temptation from outsider. In general, couples in this parish have a positive effort in internalizing their marriage vows with the awareness on the challenges in this digital era.